THE DEVELOPMENT OF THE CRIME OF MONEY LAUNDERING AND ITS IMPACT ON THE ECONOMIC AND BUSINESS SECTOR - Abdul Kadir; Reza Doris Perdana; Paiz Arif Rahman; Sandih Sandih; Rifqi Satya Anggoro; Ar Ridho M Akbar (Indonesian Journal of Law and Policy Studies, 2021)
One of the criminal acts of money laundering is known as a white collar crime that has been committed since 1867. This crime has a negative impact on the lives of people engaged in the economic and business sectors, where this crime is committed by using the financial system, namely criminal act and eliminating the origin of proceeds from criminal acts. Criminals can take advantage of financial institutions such as investing and transferring money from money laundering obtained through corruption, committing fraud, buying traveler's checks, mutual funds, bribes, crimes in banking, capital markets, stocks and financial instruments. The crime of money laundering has a tremendous impact and even threatens the country's economic stability. In this study, information on developments related to the crime of money laundering and its impact on the economic and business sectors is informed.